Intensity of recreational physical activity in different life periods in relation to breast cancer among women in the region of Western Pomerania - Kruk, Joanna (Contemporary Oncology/Współczesna Onkologia, 2012)
Background: Recreational physical activity has been consistently associated with lower breast cancer risk, but there is a need to study the intensity and duration of activity that are critical to reduce the risk. The aim of this study was to examine the influence of moderate and vigorous intensity of recreational physical activity performed at different age periods on breast cancer risk. Material and methods: The case-control study included 858 women with histological confirmation of invasive breast cancer and 1085 women free of any cancer diagnosis, residents of the region of Western Pomerania, aged 28–79 years. The frequency, duration and intensity of lifetime household, occupational and recreational physical activity, sociodemographic characteristics, reproductive factors, family history of breast cancer, current weight and height, and lifestyle habits were measured using a self-administered questionnaire. Unconditional logistic regression analyses were applied to estimate odds ratios (ORs) and 95% confidence intervals (CIs). The risk estimates were controlled for potential risk factors and lifetime household and occupational activities. Results: We found a risk reduction for recreational activity done early in life (age periods 14–20, 21–34, 35–50 years), particularly at ages 14–20 and 21–34 years, regardless of intensity. Active women engaging in more than 4.5 hours per week of moderate activity during ages 14–20 years had, on average, a 36% lower risk (OR = 0.64, 95% CI: 0.45–0.89) than women who were never or rarely active. For the women who reported 4.5 hours per week of vigorous activity during this period we found about 64% risk reduction (OR = 0.36, 95% CI: 0.26–0.51). For the period after 50 years of age, recreational activity of moderate or vigorous intensity was not significantly associated with the risk. Conclusion : Recreational physical activity of moderate or vigorous intensity done during adolescence, early and middle adulthood, particularly at ages 14–20 and 21–34 years, is associated with significantly decreased breast cancer risk.